2009
DOI: 10.1021/la901692a
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilicity in Homopolymer Surfaces Reduces Nonspecific Protein Adsorption

Abstract: Amphiphilic homopolymer films have been immobilized onto substrates to study the interactions of these polymers with proteins. X-ray photoelectron spectroscopy (XPS) was utilized to measure the amount of protein adsorption. Amphiphilic homopolymers have been shown to reduce protein adsorption, despite the high affinity of the hydrophobic or hydrophilic functional groups by themselves toward proteins. This protein resistant property seems to arise from the unique molecular scale alternation of incompatible func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…In addition, the proteins with plentiful charges from different amino acids could be easily to adhere to the PSANMs surface due to electrostatic interactions . As illustrated in Figure , after the PSANMs were cultured in plasma, their negative charge remarkably decreased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the proteins with plentiful charges from different amino acids could be easily to adhere to the PSANMs surface due to electrostatic interactions . As illustrated in Figure , after the PSANMs were cultured in plasma, their negative charge remarkably decreased.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the proteins with plentiful charges from different amino acids could be easily to adhere to the PSANMs surface due to electrostatic interactions. [41,42] As illustrated in Figure 4, after the PSANMs were cultured in plasma, their negative charge remarkably decreased. All bare PSANMs showed > 40 % decrease in negative charge (Table S4), suggesting that negatively charged PSANMs caused severe non-specific protein adsorption.…”
Section: Anti-biofouling Effect Of Pegylated Psanmsmentioning
confidence: 99%
“…Chen et al [29] studied the interactions of amphiphilic polymers films with proteins and found that despite the high affinity of the hydrophilic or hydrophobic functional groups by themselves toward proteins, the films showed great reduced nonspecific protein adsorption. Colak et al [26] designed a series of novel zwitterion-based, amphiphilic coatings.…”
Section: Introductionmentioning
confidence: 99%
“…[35,36] Indeed, polymer surfaces modified by amphiphilic materials with delicate balance in every repeat unite can present magnificent protein adsorption resistance. [37] Therefore, we hypothesized that amphiphilic surfactant-containing polymer surfaces will obtain a low protein adsorption as well as a promising hemocompatibility. To test this hypothesis, two types of sugar-based trisiloxane surfactants were synthesized as potential surface modifiers.…”
Section: Introductionmentioning
confidence: 99%